Virtually identical does not mean exactly identical: Discrepancy in energy metabolism between glucose and fructose fermentation influences the reproductive potential of yeast cells - Maślanka, Roman; Bednarska, Sabina; Zadrąg-Tęcza, Renata (Archives of Biochemistry and Biophysics, 2024)
The physiological efficiency of cells largely depends on the possibility of metabolic adaptations to changing conditions, especially on the availability of nutrients. Central carbon metabolism has an essential role in cellular function. In most cells is based on glucose, which is the primary energy source, provides the carbon skeleton for the biosynthesis of important cell macromolecules, and acts as a signalling molecule. The metabolic flux between pathways of carbon metabolism such as glycolysis, pentose phosphate pathway, and mitochondrial oxidative phosphorylation is dynamically adjusted by specific cellular economics responding to extracellular conditions and intracellular demands. Using Saccharomyces cerevisiae yeast cells and potentially similar fermentable carbon sources i.e. glucose and fructose we analyzed the parameters concerning the metabolic status of the cells and connected with them alteration in cell reproductive potential. Those parameters were related to the specific metabolic network: the hexose uptake - glycolysis and activity of the cAMP/PKA pathway - pentose phosphate pathway and biosynthetic capacities - the oxidative respiration and energy generation. The results showed that yeast cells growing in a fructose medium slightly increased metabolism redirection toward respiratory activity, which decreased pentose phosphate pathway activity and cellular biosynthetic capabilities. These differences between the fermentative metabolism of glucose and fructose, lead to long-term effects, manifested by changes in the maximum reproductive potential of cells.
Author Accepted Manuscript
Keywords: fructose vs glucose; reproductive potential; cellular metabolism; mitochondrial respiration; carbon catabolite repression; hexokinase